Predictive modelling of pH and dissolved metal concentrations and speciation following mixing of acid drainage with river water. (August 2015) - Mosley, Luke M.; Daly, Rob; Palmer, David; Yeates, Peter; Dallimore, Chris; Biswas, Tapas; Simpson, Stuart L.
Highlights: Acid drainage discharges create severe environmental impacts. pH and dissolved metal concentrations during mixing with river water were modelled. Solid phase, inorganic and organic Al and Fe speciation could also be predicted. A 3-D river hydro-geochemical model with multiple acid inputs was developed. Abstract: Discharge of acidic drainage from mining operations or acid sulphate soils can create severe environmental impacts if not managed appropriately. We tested different hydro-geochemical models to predict pH and dissolved Al, Fe and Mn concentrations and speciation following discharge and mixing of acid drainage into receiving waters; (1) an end member mixing approach using the geochemical model PHREEQC could accurately predict ( r 2 > 0.9) pH and dissolved metal concentrations at various dilutions over a pH range of 2–7, (2) dissolved inorganic and organic, and solid phase, Al and Fe speciation could be predicted using the geochemical model Visual MINTEQ (at 10% dilution), although poorer results were observed for Mn and drainage mixtures with lower metal concentrations, (3) PHREEQC gave similar results to a 3-D hydro-biogeochemical model (ELCOM-CAEDYM) when tested on a small-scale, and (4) ELCOM-CAEDYM successfully predicted dissolved metal concentrations ( r 2 ⩾ 0.8), and to some extent pH ( r 2 = 0.2), over a 5 month period in a 90 km reach of the River Murray (South Australia) with over ten acid drainage discharges. The 3-D model was also used to assess river management scenarios and this highlighted a risk for dissolved Mn exceeding (aesthetic) drinking water guidelines in the river water at low flows. Limitations of the various models are discussed and we conclude that geochemical modelling is a useful tool to predict water quality impacts following discharge of acidic drainage to natural waters.